Prefabricated brick for coke tank cone section and preparation method thereof
By reasonably preparing materials such as high-alumina bauxite, silicon carbide, etc. in prefabricated bricks for cone sections of coke cans, the problems of poor thermal shock resistance, poor wear resistance, poor peel resistance and insufficient compressive strength of existing prefabricated bricks are solved, and higher wear resistance, thermal shock resistance, peel resistance and compressive strength are achieved.
Patent Information
- Application Number
- CN202510019882.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials in the coking industry, and particularly relates to a prefabricated brick for a coke tank cone section and a preparation method thereof. Background Art
[0002] Precast bricks have been used more and more widely in recent years, especially in thermal kilns on blast furnaces, hot blast furnaces, heating furnaces, and electric furnace tops. In addition, precast bricks also play an important role in urban infrastructure construction, such as the construction of sidewalks and square infrastructure. Precast bricks have a short manufacturing cycle and are easy to install. Through mold shaping, they greatly reduce construction time and labor costs on the construction site; precast bricks have consistency, stability and reliability, which can improve the quality of buildings; precast bricks can achieve different architectural forms and styles through different designs and materials; with the continuous advancement of technology and the continuous development of the market, the application field of precast bricks will continue to expand.
[0003] Coke dry quenching is a very important part of the coking process. Coke dry quenching refers to a production process that uses recycled inert gas to cool red coke in a closed system and recovers the waste heat of coke. There is no pollutant emission during the production process, which achieves energy conservation and environmental protection. It has greater advantages than traditional wet coke quenching in improving coke quality, recycling energy and protecting the environment. The main body of coke dry quenching mainly includes two parts: a dry quenching furnace and a waste heat boiler. The coke tank is one of the important red coke transportation equipment in the dry quenching furnace. It receives the red coke at about 1000℃ pushed out of the coke oven, runs to the top of the coke quenching chamber through the traction device and the lifting device, and is discharged into the coke quenching chamber by the coke loading device.
[0004] The existing prefabricated bricks used for the cone section of the coke tank have the disadvantages of poor thermal shock resistance, poor wear resistance, poor spalling resistance and insufficient compressive strength. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a prefabricated brick for a coke drum cone section and a preparation method thereof, which has good wear resistance, thermal shock resistance, spalling resistance and compressive strength.
[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: the prefabricated bricks for the cone section of the coke drum include the following components by mass percentage: 48-69% of high-alumina bauxite, 3-9% of silicon carbide with a fineness of 0-1mm, 3-7% of silicon carbide with a fineness of 100-300 meshes, 3-9% of brown corundum with a fineness of 0-1mm, 3-8% of white corundum with a fineness of 100-300 meshes, 1-5% of white mud with a fineness of 100-300 meshes, 2-6% of silicon micropowder with a fineness of 100-300 meshes, 2-6% of 1-3mm ceramic fiber blanket crushed materials, 1-3% of precipitated barium sulfate with a fineness of 100-300 meshes, 1-5% of pure calcium aluminate cement, and 1-5% of aluminate cement;
[0007] The mass ratio of silicon carbide with a fineness of 0~1mm and brown corundum with a fineness of 0~1mm is 1:0.5~1.5, the mass ratio of white mud with a fineness of 100~300, silicon micropowder with a fineness of 100~300 and silicon carbide with a fineness of 100~300 is 3:3.5~4.5:4.5~5.5, and the mass ratio of pure calcium aluminate cement and aluminate cement is 1:0.5~1.5.
[0008] Calculated by mass percentage, the invention comprises the following components: 14-18% of high alumina with a fineness of 5-8mm, 10-15% of high alumina with a fineness of 3-5mm, 8-12% of high alumina with a fineness of 1-3mm, 8-12% of high alumina with a fineness of 0-1mm, 8-12% of high alumina with a fineness of 100-300 meshes, 3-9% of silicon carbide with a fineness of 0-1mm, 3-7% of silicon carbide with a fineness of 100-300 meshes, 3-9% of brown corundum with a fineness of 0-1mm, 3-8% of white corundum with a fineness of 100-300 meshes, 1-5% of white mud with a fineness of 100-300 meshes, 2-6% of silicon micropowder with a fineness of 100-300 meshes, 2-6% of ceramic fiber blanket fragments with a fineness of 1-3mm, 1-3% of precipitated barium sulfate with a fineness of 100-300 meshes, 1-5% of pure calcium aluminate cement, and 1-5% of aluminate cement.
[0009] 8-12% of high alumina with a fineness of 100-300 mesh, 3-8% of white corundum with a fineness of 100-300 mesh, 3-7% of silicon carbide with a fineness of 100-300 mesh, 1-5% of white mud with a fineness of 100-300 mesh and 2-6% of silicon micropowder with a fineness of 100-300 mesh, and the preferred fineness is 200 mesh.
[0010] The precipitated barium sulfate has a fineness of 200 mesh; the precipitated barium sulfate with a fineness of 200 mesh is an inorganic non-metallic material with a refractoriness of not less than 1580°C. The precipitated barium sulfate is defined as a refractory material, which has good high temperature resistance, good high temperature mechanical properties, good volume stability, and resistance to corrosion by various corrosive slags and gases. The precipitated barium sulfate with a fineness of 200 mesh can be used as a filler and can also play a reinforcing role. The addition of precipitated barium sulfate with a fineness of 100-300 mesh in the present invention can further improve its compressive strength on the basis of a reasonable mass ratio of brown corundum with a fineness of 0-1 mm and silicon carbide with a fineness of 0-1 mm, while improving its stability and corrosion resistance.
[0011] The high temperature mentioned in the present invention is 1200-1500°C; the medium temperature is 800-1200°C; and the normal temperature is 10-30°C.
[0012] High-alumina of various finenesses as a skeleton can achieve reasonable particle grading, improve its compressive strength, durability and refractoriness, and is suitable for refractory products in high temperature environments. It can improve density and crack resistance, reduce shrinkage and cracking, and extend service life.
[0013] Silica powder has excellent filling and cohesion bonding effects. The filling effect reduces pores, reduces water demand, increases volume density and reduces apparent porosity, so that the voids left after drying are reduced and the apparent porosity is reduced, thereby improving its compressive strength and high-temperature performance. Secondly, through cohesion bonding, silica powder forms Si-OH bonds similar to silica gel structure on the surface after hydration. These bonds are dehydrated and polymerized into long chains of micropowders bonded by Si-O-Si bonds during the drying process, forming a network-like Si-O-Si bonded structure. This structure is not easy to break at high temperatures, which improves the medium-temperature compressive strength. The silica powder with a fineness of 200 mesh has fine particles, large surface free energy and high activity, which makes it easier to undergo solid-phase sintering reactions at medium and high temperatures, and undergo mullite reaction with Al2O3 in high-alumina bauxite materials, thereby improving compressive strength and high-temperature performance.
[0014] White clay contains a high proportion of refractory components, such as kaolin, which can maintain structural stability at high temperatures, thereby improving refractory performance. Some components in white clay react chemically with the molten material at high temperatures to form a protective layer to prevent further erosion by the molten material, thereby improving slag resistance. White clay can increase the plasticity of refractory materials, making them easy to shape and process; white clay can also act as a binder to enhance the internal bonding force of the material and improve the overall compressive strength of the material.
[0015] Adding white mud with a fineness of 100-300, silicon micropowder with a fineness of 100-300 and silicon carbide with a fineness of 100-300 in a reasonable mass ratio can play a role in dispersion strengthening and whisker toughening, thereby improving the thermal shock resistance.
[0016] At 800℃~1100℃, CA50 aluminate cement shrinks in volume and forms internal pores due to chemical reactions; before 900℃, 90% of free water and part of bound water are removed, and its compressive strength decreases slightly, while the apparent porosity increases greatly. The remaining 6~10% of bound water is bound water that enters the coordination structure in the form of hydroxyl groups. When it is removed between 800℃~1100℃, the original lattice is destroyed and a new structure is formed, namely CaO·Al2O3 and CaO·2Al2O3. Due to the low temperature, the sintering effect is not obvious, and its structure is loose, so the compressive strength decreases significantly.
[0017] Adding CA70 aluminate cement to CA50 aluminate cement has a higher aluminum content and produces a chemical reaction with expansion effect at 800℃~1100℃, which can compensate for the decrease in compressive strength at 800℃~1100℃ due to volume shrinkage; the chemical reaction formula is as follows:
[0018] (1) CaO+Al2O3=CaO·Al2O3;
[0019] (2) CaO·Al2O3+Al2O3=CaO·2Al2O3;
[0020] After calculation, the volume expansion effect of formula (1) is 19.6%, while that of formula (2) is 12.86%. After adding a-AL2O3 to cement refractory castables, the shrinkage compensation effect is increased, that is, the expansion rate is increased, and the medium-temperature compressive strength does not decrease but increases; the medium-temperature compressive strength of CA50 aluminate cement decreases less, and its decrease rate is only 12%; it is more effective in reducing costs than using CA70 aluminate cement alone.
[0021] Brown corundum with a fineness of 0~1mm has a Mohs hardness of 9.0, which enables it to maintain high wear resistance under high temperature and high pressure environments; Brown corundum with a fineness of 0~1mm has high compressive strength, can withstand greater pressure and impact, maintain shape stability, reduce abrasive breakage and abrasive particle falling; Brown corundum has good stability to acid and alkali solutions and is not easily corroded.
[0022] The Mohs hardness of silicon carbide reaches 9.5, which can enhance fire resistance, corrosion resistance and oxidation resistance, reduce apparent porosity, improve density and stability; it can generate mullite crystal phase, enhance compressive strength, thereby improving overall compressive strength and wear resistance, which makes it extremely wear-resistant under high temperature and high pressure environment; improve overall performance and extend service life. Silicon carbide with a fineness of 0~1mm has the best wear resistance and has a synergistic effect with 0~1mm silicon carbide brown corundum within a certain mass ratio range, which can effectively improve its wear resistance.
[0023] Brown corundum with a fineness of 0~1mm and silicon carbide with a fineness of 0~1mm work together to improve its wear resistance. Adjust the mass ratio of the two, and the mass of silicon carbide with a fineness of 0~1mm and brown corundum with a fineness of 0~1mm is in the range of 1:0.5~1.5, and the wear resistance is optimal. Adding both at the same time has a longer service life than adding silicon carbide with a fineness of 0~1mm alone, and the price of brown corundum with a fineness of 0~1mm is relatively low.
[0024] When the temperature is higher than 800℃, the specific chemical reaction of silicon carbide oxidation: silicon carbide reacts with oxygen to form a silicon dioxide film;
[0025] The specific chemical reaction equation is:
[0026] SiC+3 / 2O2=SiO2+CO or SiC+2O2=SiO2+CO2.
[0027] The generated silicon dioxide film has a certain protective effect and can prevent further oxidation. However, between 800 and 1140°C, the silicon dioxide film undergoes a volume change due to phase change, causing its structure to become loose, and the oxidation protection effect is weakened. After long-term use, the structure becomes loose and peeling occurs.
[0028] Brown corundum with a fineness of 0~1mm is relatively low in price, has stable performance at medium and high temperatures, and has good antioxidant properties. Brown corundum with a fineness of 0~1mm and silicon carbide with a fineness of 0~1mm work synergistically to enhance wear resistance and medium stability, and increase its medium temperature service life.
[0029] The pure calcium aluminate cement is CA70 aluminate cement, and the aluminate cement is CA50 aluminate cement. CA70 aluminate cement has a higher alumina content and fewer impurities. The setting characteristics and refractoriness of CA70 aluminate cement are better than those of CA50 aluminate cement. CA70 aluminate cement and CA50 aluminate cement are used in combination. Through reasonable proportioning, the mass proportion of pure calcium aluminate cement and aluminate cement is 1:0.5~1.5, which can enhance the medium-temperature compressive strength. Although CA70 aluminate cement has superior performance, it is more expensive, while CA50 aluminate cement is relatively cheaper, which reduces material costs while ensuring performance.
[0030] According to another aspect of the present invention, a method for preparing prefabricated bricks for a coke tank cone section is also provided, comprising the following steps:
[0031] (1) High alumina with a fineness of 5-8 mm: 14-18%, high alumina with a fineness of 3-5 mm: 10-15%, high alumina with a fineness of 1-3 mm: 8-12%, high alumina with a fineness of 0-1 mm: 8-12%, high alumina with a fineness of 100-300 mesh: 8-12%, silicon carbide with a fineness of 0-1 mm: 3-9%, silicon carbide with a fineness of 100-300 mesh: 3-7%, and fineness of 3-9% of brown corundum with a fineness of 0-1 mm, 3-8% of white corundum with a fineness of 100-300 meshes, 1-5% of white mud with a fineness of 100-300 meshes, 2-6% of silica powder with a fineness of 100-300 meshes, 2-6% of 1-3 mm ceramic fiber blanket scraps, 1-3% of precipitated barium sulfate with a fineness of 100-300 meshes, 1-5% of pure calcium aluminate cement and 1-5% of aluminate cement are mixed to obtain component A;
[0032] (2) Mix component A and the composite water reducer to obtain component B;
[0033] (3) Mixing component B and water and casting to obtain a blank;
[0034] (4) The blank is left to stand for demoulding, curing, and baking to obtain prefabricated bricks for the cone section of the coke tank.
[0035] The mixing temperature in step (1) is 15-25°C and the mixing time is 2-4 minutes to ensure that the components are evenly distributed and the stability is guaranteed.
[0036] The mass of the composite water reducer in step (2) is 0.2-0.3% of component A; the composite water reducer can reduce water demand and improve compressive strength. Excessive use of the composite water reducer will lead to reduced compressive strength and durability. Too little use of the composite water reducer will increase water demand, and even lead to segregation, bleeding, and hardening, and reduce compressive strength and service life.
[0037] The composite water reducer described in step (2) is composed of sodium lignin sulfonate, sodium tripolyphosphate and sodium hexametaphosphate; the mass of sodium lignin sulfonate accounts for 40% of the mass of the composite water reducer, the mass of sodium tripolyphosphate accounts for 40% of the mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 20% of the mass of the composite water reducer. First, sodium lignin sulfonate, sodium tripolyphosphate and sodium hexametaphosphate are mixed to obtain a composite water reducer, and then component A and the composite water reducer are mixed. Sodium lignin sulfonate can improve the performance of prefabricated bricks for coke tank cone sections, and improve the compressive strength and durability of prefabricated bricks for coke tank cone sections. Sodium tripolyphosphate can improve fluidity, reduce water demand without flocculation and precipitation, and is easy to operate. Sodium hexametaphosphate can reduce water, thicken, improve compressive strength and improve fluidity. The simultaneous use of the three has a synergistic effect, which reduces the water demand to a minimum, which is an effect that cannot be achieved when the three are used alone, and at the same time improves the compressive strength at room temperature.
[0038] The mass of the water in step (3) is 4.5-5.5% of component A; adding water can improve the compressive strength of the refractory castable. After adding water, a hydration reaction occurs, forming a new physical hardened structure, which improves the compressive strength. The refractory castable needs to have a certain fluidity during construction to facilitate pouring and tamping; adding an appropriate amount of water can improve its fluidity, making it easier to construct and shape.
[0039] Adding too much water will lead to a decrease in compressive strength. Excessive water will lead to an incorrect water-cement ratio, causing water to seep to the surface, affecting the internal structure and performance of the precast bricks for the cone section of the coke tank. Adding too much water will extend the setting time. Excessive water will extend the setting time and affect the demolding time, which will extend the construction period and increase the difficulty and cost of construction. Adding too much water will lead to a decrease in construction quality. Adding too much water will lead to uneven mixing, loose structure, and decreased construction quality. Improper mixing will lead to the formation of agglomerates, further affecting the compressive strength and performance of the castable. Adding too much water will lead to water seepage, which is the phenomenon that water separates from the precast bricks for the cone section of the coke tank, affecting the internal structure and quality of the precast bricks for the cone section of the coke tank. Adding too little water will cause the compressive strength of the precast bricks for the cone section of the coke tank to fail to meet the standard, and normal hydration cannot be carried out, affecting the quality of the entire project.
[0040] The temperature of the demoulding in step (4) is 10-25°C, and the demoulding time is 7-9h. If the temperature is too low and the static time is too short, cracking will occur; if the temperature is too high and the static time is too long, demoulding will be difficult.
[0041] The curing temperature in step (4) is 10-25°C and the curing time is 8-12 hours. Curing at a temperature that is too high or too low will result in a decrease in compressive strength, and reduce product performance and life.
[0042] After the coke drum cone section is formed with precast bricks, the compressive strength mainly depends on the hydration reaction of cement. The curing temperature is 10~25℃. The hydration products of cement are metastable hydrated monocalcium aluminate, hydrated dicalcium aluminate and trihydrated alumina. The cement hydration rate is the fastest in this temperature range, so calcium aluminate cement can achieve rapid solidification and reach the highest compressive strength within 8~12 hours under 10~25℃ conditions.
[0043] The baking temperature in step (4) is 100-120°C and the baking time is 18-30 hours. If the baking temperature is too high, the water vapor will be discharged too quickly, micro cracks will appear in the prefabricated bricks, and the service life will be shortened; if the baking temperature is too low, the drying will not be thorough, the compressive strength will decrease, the product quality will be unstable, and the service life will be shortened.
[0044] During the baking process of the prefabricated bricks for the cone section of the coke drum at 100-120°C, the rehydration of the residual hydratable phase in the castable will be promoted, the number of hydration products generated will increase, and the hydration process will be completed. Preferably, the baking temperature is 110°C and the baking time is 24h; after the preferred baking temperature and time, the compressive strength reaches the highest value.
[0045] The baking temperature in step (4) is 100-120° C., and the baking time is 18-24 hours. If the baking temperature is too high, the compressive strength will decrease, the quality will be unstable, and the service life will be shortened. If the baking temperature is too low, the drying will be incomplete, the quality will be reduced, the production efficiency will be low, and the energy consumption will increase.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] 1. The present invention reasonably designs the mass ratio of silicon carbide with a fineness of 0-1mm and brown corundum with a fineness of 0-1mm, which can improve its wear resistance; by adding white mud with a fineness of 100-300 mesh, silicon micropowder with a fineness of 100-300 mesh and silicon carbide with a fineness of 100-300 mesh in a reasonable mass ratio, its thermal shock resistance can be improved; the mass ratio of pure calcium aluminate cement and aluminate cement is reasonably adjusted to improve its compressive strength. The purpose of mixing raw materials with various finenesses is to achieve a reasonable particle grading, thereby achieving the most compact stacking, reducing porosity, forming a dense structure, improving anti-stripping performance and extending its service life.
[0048] 2. The composite water reducing agent of the present invention is composed of sodium lignin sulfonate, sodium tripolyphosphate and sodium hexametaphosphate. The synergistic effect of the three reduces the water demand to the minimum and improves the compressive strength at room temperature.
[0049] 3. The addition of precipitated barium sulfate with a fineness of 100-300 meshes in the present invention can further improve its compressive strength on the basis of a reasonable mass ratio of brown corundum with a fineness of 0-1 mm and silicon carbide with a fineness of 0-1 mm, while improving its stability and corrosion resistance; the addition of ceramic fiber blanket crushed materials can effectively improve its thermal insulation performance. DETAILED DESCRIPTION
[0050] The present invention will be further described below with reference to specific embodiments and comparative examples.
[0051] Embodiment 1 is the best embodiment of the present invention, and the present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0052] The chemical additives used in the examples and comparative examples of the present invention are all commercially available, and their specific information is as follows:
[0053] High alumina with a fineness of 5~8mm: refers to 80 high alumina with a fineness of 5~8mm, industrial grade, Yihui Refractory Material Business Department, Linchi Town, Zouping City;
[0054] High alumina with a fineness of 3~5mm: refers to 80 high alumina with a fineness of 3~5mm, industrial grade, Yihui Refractory Material Business Department, Linchi Town, Zouping City;
[0055] High alumina with a fineness of 1~3mm: refers to 80 high alumina with a fineness of 1~3mm, industrial grade, Yihui Refractory Material Business Department, Linchi Town, Zouping City;
[0056] High alumina with a fineness of 0~1mm: refers to 80 high alumina with a fineness of 0~1mm: industrial grade, Yihui Refractory Material Business Department, Linchi Town, Zouping City;
[0057] High alumina with a fineness of 100~300 mesh: refers to 80 high alumina with a fineness of 100~300 mesh: industrial grade, Yihui Refractory Material Business Department, Linchi Town, Zouping City;
[0058] Silicon carbide with a fineness of 0-1 mm: industrial grade, purchased from Botianhong Abrasive Co., Ltd.;
[0059] Brown corundum with a fineness of 0-1 mm: industrial grade, purchased from Botianhong Abrasive Co., Ltd.;
[0060] White corundum with a fineness of 100-300 mesh: industrial grade, purchased from Botianhong Abrasive Co., Ltd.;
[0061] Silicon carbide with a fineness of 100-300 mesh: industrial grade, purchased from Botianhong Abrasive Co., Ltd.;
[0062] The white mud with a fineness of 100-300 mesh refers to Guangxi Weiluo white mud, industrial grade, purchased from Zibo Niu Niu Trading Co., Ltd.;
[0063] Silica powder with a fineness of 100-300 mesh, industrial grade, purchased from Zibo Lupai Trading Co., Ltd.;
[0064] Precipitated barium sulfate with a fineness of 100-300 mesh: industrial grade, purchased from Henan Chaonuo Chemical Co., Ltd.;
[0065] Ceramic fiber blanket scraps: industrial grade, purchased from Donghuibang Energy Saving Materials Co., Ltd.;
[0066] Pure calcium aluminate cement, industrial grade, purchased from Zibo Lupai Trading Co., Ltd.;
[0067] Aluminate cement, industrial grade, purchased from Zibo Lupai Trading Co., Ltd.;
[0068] Sodium lignin sulfonate, industrial grade, was purchased from Henan Muxu Chemical Co., Ltd.;
[0069] Sodium tripolyphosphate, industrial grade, purchased from Zibo Lupai Trading Co., Ltd.;
[0070] Sodium hexametaphosphate, industrial grade, was purchased from Zibo Lupai Trading Co., Ltd.
[0071] Example 1
[0072] A formula for prefabricated bricks for a coke drum cone section, comprising the following components in percentage by mass: 16% high-alumina bauxite with a fineness of 5-8 mm, 13% high-alumina bauxite with a fineness of 3-5 mm, 10% high-alumina bauxite with a fineness of 1-3 mm, 10% high-alumina bauxite with a fineness of 0-1 mm, 6% silicon carbide with a fineness of 0-1 mm, 6% brown corundum with a fineness of 0-1 mm, 10% high-alumina bauxite with a fineness of 200 meshes, 5% white corundum with a fineness of 200 meshes, 3% white mud with a fineness of 200 meshes, 4% silicon micropowder with a fineness of 200 meshes, 5% silicon carbide with a fineness of 200 meshes, 4% ceramic fiber blanket scraps with a fineness of 1-3 mm, 2% precipitated barium sulfate with a fineness of 200 meshes, 3% pure calcium aluminate cement, and 3% aluminate cement;
[0073] The preparation method comprises the following steps:
[0074] (1) Mix high alumina with a fineness of 5-8 mm, high alumina with a fineness of 3-5 mm, high alumina with a fineness of 1-3 mm, high alumina with a fineness of 0-1 mm, silicon carbide with a fineness of 0-1 mm, brown corundum with a fineness of 0-1 mm, high alumina with a fineness of 200 mesh, white corundum with a fineness of 200 mesh, silicon carbide with a fineness of 200 mesh, white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh, precipitated barium sulfate with a fineness of 200 mesh, ceramic fiber blanket crushed material with a fineness of 1-3 mm, pure calcium aluminate cement and aluminate cement at 20° C. for 3 min to obtain component A;
[0075] (2) Mix component A and 0.25% of composite water reducer to obtain component B;
[0076] (3) Mix component B and 5% water and cast them into a blank;
[0077] (4) The blank is left to stand at 15°C for 8 hours before demolding. The curing temperature is 20°C for 10 hours and the baking temperature is 110°C for 24 hours to obtain prefabricated bricks for the cone section of the coke tank.
[0078] Example 2
[0079] The difference from Example 1 is that the formula of prefabricated bricks for the cone section of the coke drum in this embodiment includes the following components, and the mass percentage of each component is: 18% high alumina with a fineness of 5-8mm, 14.5% high alumina with a fineness of 3-5mm, 10% high alumina with a fineness of 1-3mm, 10% high alumina with a fineness of 0-1mm, 6% silicon carbide with a fineness of 0-1mm, 3% brown corundum with a fineness of 0-1mm, 10% high alumina with a fineness of 200 mesh, 5% white corundum with a fineness of 200 mesh, 3% white mud with a fineness of 200 mesh, 3.5% silicon micropowder with a fineness of 200 mesh, 4.5% silicon carbide with a fineness of 200 mesh, 4% ceramic fiber blanket fragments with a fineness of 1-3mm, 2% precipitated barium sulfate with a fineness of 200 mesh, 3% pure calcium aluminate cement, and 1.5% aluminate cement.
[0080] Example 3
[0081] The difference from Example 1 is that the formula of prefabricated bricks for the cone section of the coke drum in this embodiment includes the following components, and the mass percentage of each component is: 14% high alumina with a fineness of 5-8mm, 10% high alumina with a fineness of 3-5mm, 9.5% high alumina with a fineness of 1-3mm, 10% high alumina with a fineness of 0-1mm, 6% silicon carbide with a fineness of 0-1mm, 9% brown corundum with a fineness of 0-1mm, 10% high alumina with a fineness of 200 mesh, 5% white corundum with a fineness of 200 mesh, 3% white mud with a fineness of 200 mesh, 4.5% silicon micropowder with a fineness of 200 mesh, 5.5% silicon carbide with a fineness of 200 mesh, 4% ceramic fiber blanket fragments with a fineness of 1-3mm, 2% precipitated barium sulfate with a fineness of 200 mesh, 3% pure calcium aluminate cement, and 4.5% aluminate cement.
[0082] Example 4
[0083] A formula for prefabricated bricks for a coke drum cone section, comprising the following components in percentage by mass: 14% high-alumina bauxite with a fineness of 5-8 mm, 10% high-alumina bauxite with a fineness of 3-5 mm, 8% high-alumina bauxite with a fineness of 1-3 mm, 8% high-alumina bauxite with a fineness of 0-1 mm, 9% silicon carbide with a fineness of 0-1 mm, 9% brown corundum with a fineness of 0-1 mm, 8% high-alumina bauxite with a fineness of 200 meshes, 3% white corundum with a fineness of 200 meshes, 5% white mud with a fineness of 200 meshes, 6% silicon micropowder with a fineness of 200 meshes, 7% silicon carbide with a fineness of 200 meshes, 2% ceramic fiber blanket scraps with a fineness of 1-3 mm, 1% precipitated barium sulfate with a fineness of 200 meshes, 5% pure calcium aluminate cement, and 5% aluminate cement;
[0084] The preparation method comprises the following steps:
[0085] (1) High alumina with a fineness of 5-8 mm, high alumina with a fineness of 3-5 mm, high alumina with a fineness of 1-3 mm, high alumina with a fineness of 0-1 mm, silicon carbide with a fineness of 0-1 mm, brown corundum with a fineness of 0-1 mm, high alumina with a fineness of 200 mesh, white corundum with a fineness of 200 mesh, silicon carbide with a fineness of 200 mesh, white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh, precipitated barium sulfate with a fineness of 200 mesh, ceramic fiber blanket crushed material with a fineness of 1-3 mm, pure calcium aluminate cement and aluminate cement are mixed at 20° C. for 3 min to obtain component A;
[0086] (2) Mix component A and 0.20% of composite water reducer to obtain component B;
[0087] (3) Component B and 4.5% water are mixed and cast to obtain a blank;
[0088] (4) The blank is left to stand at 15°C for 8 hours before demolding. The curing temperature is 20°C for 10 hours and the baking temperature is 110°C for 24 hours to obtain prefabricated bricks for the cone section of the coke tank.
[0089] Example 5
[0090] A formula for prefabricated bricks for a coke drum cone section, comprising the following components in percentage by mass: 18% of high-alumina bauxite with a fineness of 5-8 mm, 15% of high-alumina bauxite with a fineness of 3-5 mm, 12% of high-alumina bauxite with a fineness of 1-3 mm, 12% of high-alumina bauxite with a fineness of 0-1 mm, 3% of silicon carbide with a fineness of 0-1 mm, 3% of brown corundum with a fineness of 0-1 mm, 12% of high-alumina bauxite with a fineness of 200 meshes, 8% of white corundum with a fineness of 200 meshes, 1% of white mud with a fineness of 200 meshes, 2% of silicon micropowder with a fineness of 200 meshes, 3% of silicon carbide with a fineness of 200 meshes, 6% of ceramic fiber blanket fragments with a fineness of 1-3 mm, 3% of precipitated barium sulfate with a fineness of 200 meshes, 1% of pure calcium aluminate cement, and 1% of aluminate cement;
[0091] The preparation method comprises the following steps:
[0092] (1) Mix high alumina with a fineness of 5-8 mm, high alumina with a fineness of 3-5 mm, high alumina with a fineness of 1-3 mm, high alumina with a fineness of 0-1 mm, silicon carbide with a fineness of 0-1 mm, brown corundum with a fineness of 0-1 mm, high alumina with a fineness of 200 mesh, white corundum with a fineness of 200 mesh, silicon carbide with a fineness of 200 mesh, white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh, precipitated barium sulfate with a fineness of 200 mesh, ceramic fiber blanket crushed material with a fineness of 1-3 mm, pure calcium aluminate cement and aluminate cement at 20° C. for 3 min to obtain component A;
[0093] (2) Mix component A and 0.30% of composite water reducer to obtain component B;
[0094] (3) Component B and 5.5% water are mixed and cast to obtain a blank;
[0095] (4) The blank is left to stand at 15°C for 8 hours before demolding. The curing temperature is 20°C for 10 hours and the baking temperature is 110°C for 24 hours to obtain prefabricated bricks for the cone section of the coke tank.
[0096] Example 6
[0097] The present embodiment has the same formula as that of embodiment 1, and the preparation method comprises the following steps:
[0098] (1) Mix high alumina with a fineness of 5-8 mm, high alumina with a fineness of 3-5 mm, high alumina with a fineness of 1-3 mm, high alumina with a fineness of 0-1 mm, silicon carbide with a fineness of 0-1 mm, brown corundum with a fineness of 0-1 mm, high alumina with a fineness of 200 mesh, white corundum with a fineness of 200 mesh, silicon carbide with a fineness of 200 mesh, white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh, precipitated barium sulfate with a fineness of 200 mesh, ceramic fiber blanket crushed material with a fineness of 1-3 mm, pure calcium aluminate cement and aluminate cement at 15° C. for 2 min to obtain component A;
[0099] (2) Mix component A and 0.25% of composite water reducer to obtain component B;
[0100] (3) Mix component B and 5% water and cast them into a blank;
[0101] (4) The blank is left to stand at 10°C for 7 hours before demolding. The curing temperature is 10°C for 8 hours. The baking temperature is 100°C for 18 hours to obtain prefabricated bricks for the cone section of the coke tank.
[0102] Example 7
[0103] The present embodiment has the same formula as that of embodiment 1, and the preparation method comprises the following steps:
[0104] (1) Mix high alumina with a fineness of 5-8 mm, high alumina with a fineness of 3-5 mm, high alumina with a fineness of 1-3 mm, high alumina with a fineness of 0-1 mm, silicon carbide with a fineness of 0-1 mm, brown corundum with a fineness of 0-1 mm, high alumina with a fineness of 200 mesh, white corundum with a fineness of 200 mesh, silicon carbide with a fineness of 200 mesh, white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh, precipitated barium sulfate with a fineness of 200 mesh, ceramic fiber blanket crushed material with a fineness of 1-3 mm, pure calcium aluminate cement and aluminate cement at 25° C. for 4 min to obtain component A;
[0105] (2) Mix component A and 0.25% of composite water reducer to obtain component B;
[0106] (3) Mix component B and 5% water and cast them into a blank;
[0107] (4) The blank is left to stand at 25°C for 9 hours before demolding. The curing temperature is 25°C for 12 hours, the baking temperature is 120°C for 30 hours, and the prefabricated bricks for the coke tank cone section are obtained.
[0108] Example 8
[0109] The difference from Example 1 is that the formula of prefabricated bricks for the cone section of the coke drum in this embodiment includes the following components, and the mass percentage of each component is: 16% high alumina with a fineness of 5-8mm, 13% high alumina with a fineness of 3-5mm, 10% high alumina with a fineness of 1-3mm, 10% high alumina with a fineness of 0-1mm, 6% silicon carbide with a fineness of 0-1mm, 6% brown corundum with a fineness of 0-1mm, 10% high alumina with a fineness of 100 mesh, 5% white corundum with a fineness of 100 mesh, 3% white mud with a fineness of 100 mesh, 4% silicon micropowder with a fineness of 100 mesh, 5% silicon carbide with a fineness of 100 mesh, 4% ceramic fiber blanket fragments with a fineness of 1-3mm, 2% precipitated barium sulfate with a fineness of 100 mesh, 3% pure calcium aluminate cement, and 3% aluminate cement.
[0110] Example 9
[0111] The difference from Example 1 is that the formula of prefabricated bricks for the coke drum cone section of this embodiment includes the following components, and the mass percentage of each component is: 16% high alumina with a fineness of 5-8mm, 13% high alumina with a fineness of 3-5mm, 10% high alumina with a fineness of 1-3mm, 10% high alumina with a fineness of 0-1mm, 6% silicon carbide with a fineness of 0-1mm, 6% brown corundum with a fineness of 0-1mm, 10% high alumina with a fineness of 300 mesh, 5% white corundum with a fineness of 300 mesh, 3% white mud with a fineness of 300 mesh, 4% silicon micropowder with a fineness of 300 mesh, 5% silicon carbide with a fineness of 300 mesh, 4% ceramic fiber blanket fragments with a fineness of 1-3mm, 2% precipitated barium sulfate with a fineness of 300 mesh, 3% pure calcium aluminate cement, and 3% aluminate cement.
[0112] Comparative Example 1
[0113] The preparation method of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that in Example 1, with the only difference being that silicon carbide with a fineness of 0-1 mm is 6%, brown corundum with a fineness of 0-1 mm is 1.2%, white mud with a fineness of 200 mesh is 3%, silicon micropowder with a fineness of 200 mesh is 3.1%, silicon carbide with a fineness of 200 mesh is 4.1%, pure calcium aluminate cement is 3%, and aluminate cement is 0.6%.
[0114] Comparative Example 2
[0115] The preparation method of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that in Example 1, with the only difference being that the silicon carbide with a fineness of 0-1 mm is 6%, the brown corundum with a fineness of 0-1 mm is 10.8%, the white mud with a fineness of 200 mesh is 3%, the silicon micropowder with a fineness of 200 mesh is 4.8%, the silicon carbide with a fineness of 200 mesh is 5.8%, the pure calcium aluminate cement is 3%, and the aluminate cement is 5.4%.
[0116] Comparative Example 3
[0117] The preparation method of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that in Example 1, except that precipitated barium sulfate with a fineness of 100-300 mesh is not added.
[0118] Comparative Example 4
[0119] The method for preparing the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that in Example 1, except that no ceramic fiber blanket fragments are added.
[0120] Comparative Example 5
[0121] The formula of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that of Example 1, with the only difference being that 0.25% sodium lignin sulfonate is added as a water reducing agent in step (2).
[0122] Comparative Example 6
[0123] The formula of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that of Example 1, except that 0.25% sodium tripolyphosphate is added as a water reducing agent in step (2).
[0124] Comparative Example 7
[0125] The formula of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that of Example 1, with the only difference being that 0.25% of sodium hexametaphosphate is added as a water reducing agent in step (2).
[0126] Comparative Example 8
[0127] The formula of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that of Example 1, except that 0.1% of the composite water reducing agent is added in step (2).
[0128] Comparative Example 9
[0129] The formula of the prefabricated bricks for the coke drum cone section described in this comparative example is the same as that of Example 1, except that 0.4% of the composite water reducing agent is added in step (2).
[0130] Performance Testing
[0131] The performance of the prefabricated bricks for the coke drum cone segments prepared in the examples and comparative examples was tested. The specific test results are shown in Table 1.
[0132] The wear amount of prefabricated bricks used in the cone section of the coke tank is tested with reference to GB / T18301-2012 "Test method for wear resistance at room temperature".
[0133] The thermal shock resistance of prefabricated bricks used in the cone section of the coke tank is tested with reference to GB / T30873-2014 "Thermal shock resistance test method".
[0134] The anti-stripping property of prefabricated bricks used in the cone section of the coke tank is tested with reference to GB / T32833-2016 "Anti-stripping property test method".
[0135] The apparent porosity of precast bricks used in the cone section of the coke tank is tested with reference to GB / T2997-2015 "Test method for apparent porosity".
[0136] The prefabricated brick permanent wire of the coke drum cone section is tested with reference to GB / T5988-2007 "Test method for changes in permanent wires caused by heating".
[0137] The compressive strength of prefabricated bricks used in the cone section of the coke tank is tested with reference to GB / T5072-2008 "Compressive Strength Test Method".
[0138] The water requirement of precast bricks for the cone section of the coke tank is tested with reference to GB / T4513.4-2017 "Determination of castable fluidity".
[0139] The test method for the tank shell external temperature is to add 1100℃ coke into the coke tank, and after 2 hours, the temperature of the tank shell is measured with a thermometer.
[0140] Table 1 Performance test results of prefabricated bricks for coke tank cone section in embodiments and comparative examples .
[0141] It can be concluded from Table 1 that the present invention reasonably designs the mass ratio of silicon carbide with a fineness of 0-1 mm and brown corundum with a fineness of 0-1 mm, which can improve its wear resistance; by adding white mud with a fineness of 100-300, silicon micropowder with a fineness of 100-300 and silicon carbide with a fineness of 100-300 in a reasonable mass ratio, its thermal shock resistance can be improved; and by reasonably adjusting the mass ratio of pure calcium aluminate cement and aluminate cement, its compressive strength at 800-1200°C can be improved. The purpose of mixing raw materials with various finenesses is to achieve a reasonable particle grading, thereby achieving the most compact stacking, reducing porosity, forming a dense structure, improving anti-stripping performance and extending its service life.
[0142] It can be seen from the results of Comparative Examples 1 and 2 that when the mass ratio of silicon carbide with a fineness of 0-1 mm and brown corundum with a fineness of 0-1 mm exceeds the range of 1:0.5-1.5, its wear resistance is reduced; when the mass ratio of white mud with a fineness of 200 mesh, silicon micropowder with a fineness of 200 mesh and silicon carbide with a fineness of 200 mesh exceeds the range of 3:3.5-4.5:4.5-5.5, its thermal shock resistance is reduced; when the mass ratio of calcium aluminate cement and aluminate cement exceeds the range of 1:0.5-1.5, its compressive strength at 800-1200°C is reduced.
[0143] It can be seen from the results of Comparative Example 3 that, without adding precipitated barium sulfate with a fineness of 100-300 mesh, the compressive strength cannot be further improved on the basis of a reasonable mass ratio of brown corundum with a fineness of 0-1 mm and silicon carbide with a fineness of 0-1 mm, nor can its stability and corrosion resistance be further improved; it can be seen from the results of Comparative Example 4 that without adding ceramic fiber blanket crushed materials, the thermal insulation effect is deteriorated.
[0144] It can be seen from the results of Comparative Examples 5, 6 and 7 that when the three are used alone as water reducers, the water reduction effect cannot reach the effect when the three are used simultaneously; sodium lignin sulfonate, sodium tripolyphosphate and sodium hexametaphosphate have a synergistic effect, which can minimize the water demand and improve the compressive strength at the same time.
[0145] It can be seen from the results of Comparative Example 8 that excessive use of the composite water-reducing agent will lead to a decrease in the compressive strength; it can be seen from the results of Comparative Example 8 that too little use of the composite water-reducing agent will lead to an increase in water demand and a decrease in the compressive strength.
[0146] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A prefabricated brick for a coke tank cone section, characterized in that: The composition comprises the following components by mass percentage: 48-69% high alumina, 3-9% silicon carbide with a fineness of 1 mm, 3-7% silicon carbide with a fineness of 100-300 meshes, 3-9% brown corundum with a fineness of 0-1 mm, 3-8% white corundum with a fineness of 100-300 meshes, 1-5% white mud with a fineness of 100-300 meshes, 2-6% silicon micropowder with a fineness of 100-300 meshes, 2-6% ceramic fiber blanket fragments with a fineness of 1-3 mm, 1-3% precipitated barium sulfate with a fineness of 100-300 meshes, 1-5% CA70 aluminate cement, and 1-5% CA50 aluminate cement; The mass ratio of silicon carbide with a fineness of 1mm and brown corundum with a fineness of 0-1mm is 1:0.5-1.5, the mass ratio of white mud with a fineness of 100-300, silicon micropowder with a fineness of 100-300 and silicon carbide with a fineness of 100-300 is 3:3.5-4.5:4.5-5.5, and the mass ratio of CA70 aluminate cement and CA50 aluminate cement is 1:0.5-1.5; The preparation method comprises the following steps: (1) Mix the above raw materials according to the proportions to obtain component A; (2) Mix component A and the composite water reducer to obtain component B; (3) Mixing component B and water and casting to obtain a blank; (4) The blank is left to stand for demoulding, curing, and baking to obtain prefabricated bricks for the cone section of the coke tank; The composite water reducer in step (2) is composed of sodium lignin sulfonate, sodium tripolyphosphate and sodium hexametaphosphate, wherein the mass of sodium tripolyphosphate accounts for 40% of the mass of the composite water reducer, and the mass of sodium hexametaphosphate accounts for 20% of the mass of the composite water reducer; The curing temperature in step (4) is 10 to 25°C, and the curing time is 8 to 12 hours.
2. The prefabricated brick for the cone section of a coke tank according to claim 1, characterized in that: In terms of mass percentage, it includes the following components: 14-18% of high-alumina bauxite with a fineness of 5-8mm, 10-15% of high-alumina bauxite with a fineness of 3-5mm, 8-12% of high-alumina bauxite with a fineness of 1-3mm, 8-12% of high-alumina bauxite with a fineness of 0-1mm, 8-12% of high-alumina bauxite with a fineness of 100-300 meshes, 3-9% of silicon carbide with a fineness of 1mm, and 3-9% of silicon carbide with a fineness of 100-300 meshes. 7%, brown corundum with a fineness of 0~1mm 3~9%, white corundum with a fineness of 100~300 mesh 3~8%, white mud with a fineness of 100~300 mesh 1~5%, silica powder with a fineness of 100~300 mesh 2~6%, ceramic fiber blanket fragments with a fineness of 1~3mm 2~6%, precipitated barium sulfate with a fineness of 100~300 mesh 1~3%, CA70 aluminate cement 1~5%, CA50 aluminate cement 1~5%.
3. The prefabricated brick for the cone section of a coke tank according to claim 1 or 2, characterized in that: The fineness of the precipitated barium sulfate is 200 meshes.
4. The prefabricated brick for the cone section of a coke tank according to claim 1, characterized in that: The mass of the composite water reducing agent in step (2) is 0.2-0.3% of component A.
5. The prefabricated brick for the cone section of a coke tank according to claim 1, characterized in that: The mass of the water in step (3) is 4.5-5.5% of component A.
6. The prefabricated brick for the cone section of a coke tank according to claim 1, characterized in that: The baking temperature in step (4) is 100-120° C., and the baking time is 18-30 hours.
Citation Information
Patent Citations
Refractory castable
CN109133883A
Quick-drying high-strength high-refractoriness-under-load castable for blast-furnace tuyere as well as preparation method and application thereof
CN113666719A
High-performance rare earth composite calcium carbide furnace cover refractory castable and preparation method thereof
CN119080483A